PROGRAM SERTIFIKASI SEBAGAI UPAYA DALAM MENINGKATKAN PROFESIONALISME GURU (Studi Kasus di SMK 2 dan SMA 3 Muhammadiyah Surakarta) - purmansyah purnamansyah (LP3M Universitas Muhammadiyah Muara Bungo, 2018)
This research is aimed to determine; 1) The characteristics of professionalism and certified teachers to pass a competency test, 2) efforts of teachers in the implementation of learning and 3) the role of the principal to improve teacher performance. This research is a descriptive research. Subject of the study consisted of a certified teacher, Headmaster. Data collection technique used observation, questionnaire, and documentation. Mechanical analysis of data through data reduction, data presentation, and decision making. The results showed: 1) Master certified and pass a competency test mastering professional competencies which include mastery of materials, structure, concept and mindset of scientific support of teaching subjects and develop professionalism in a sustainable manner by taking action reflective. Teachers master pedagogic competence which includes mastery of the characteristics of learners, mastering learning theory and principles of educational learning, curriculum development, implementing the learning activities that educate, communicate with students and conducting assessment or evaluation. 2) As an attempt to overcome these barriers are: a) to optimize the use of various methods and learning media are varied and provide reinforcement or appreciation to students who ask and who has answered the question, b) The role of the principal to improve teacher performance are: Sought to find another solution for the learning process continues to run smoothly in accordance with lesson plans that have been made so as not to harm the students. Implementation of learning undertaken by teachers has been good functionally, technically tatapi lies in the low motivation and activeness in the learning process, in addition to the management of infrastructure is not maximized learning.